(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2023)
Background: Reactionary hemorrhage is a severe complication of a cesarean section (CS) that may result from uterine atony, retained placental tissue, or ligature slippage. This case presents a rare cause of reactionary hemorrhage due to focal placenta invasion after CS presenting as hemoperitoneum. Case presentation: A 32-year gravida 2 para 1 presented to the outpatient department at 39 gestational weeks. She was scheduled for elective CS and bilateral tubectomy given previous CS and cephalopelvic disproportion. Her antenatal routine ultrasound was unremarkable. Eight hours later, she was scheduled for an emergency relaparotomy for intraabdominal collection. Intraoperatively, there was bleeding from a focal placental invasion at the left cornua with omentum covering the placental mass and massive hemoperitoneum. She was transfused with 4, 4, and 6 units of packed cells, platelets, and fresh frozen plasma, respectively, and was discharged home. Conclusion: Focal placenta percreta may present with hypotension and massive hemorrhage in the postpartum period; therefore, a high index of suspicion is required to detect and prevent complications intrapartum.